The Effect of Educational Training and Teacher Professional Training in Improving Teacher Professional Competence at SMA Negeri 2 Bantaeng - Andi Sugiati (Universitas of Muhammadiyah Makassar, 2022)
This study aimed to determine the effect of teacher professional education and training (PLPG) in improving teacher competence. This research is motivated by the lack of teacher competence, so researchers want to examine the effect of educational training and teacher professional training (PLPG) in improving professional competence. The type of research used was quantitative research with data collection techniques using observation, documentation and questionnaires. The data analysis technique used quantitative data analysis techniques. The results showed that the educational training and teacher professional training (PLPG) affected teacher competence, this was seen from the significance value of 0.001 with the t-test value of 1.196. Based on the established criteria, if the significance is 0.001 0.005, then H0 is rejected, which means there is no influence of teacher professional education and training (PLPG) with teacher competence. At the same time, H11 is accepted, indicating that teacher professional education and training (PLPG) influences teacher professional competence.Penelitian ini dilatarbelakangi masih kurangnya kompetensi guru sehingga peneliti ingin meneliti pengaruh pelatihan PLPG dalam meningkatkan kompetensi profesional. Tujuan penelitian ini adalah untuk mengetahui pengaruh PLPG dalam meningkatkan kompetensi guru jenis penelitian yang di gunakan adalah penelitian kuantitatif dengan teknik pengumpulan data menggunakan cara observasi, dokumentasi dan angket. Teknik analisis data menggukan teknik analisis data kuantitatif. Hasil penelitian menunjukkan bahwa pelatihan PLPG memberi pengaruh terhadap kompetensi guru, hal ini dilihat dari nilai signifikansi 0,001 dengan nilai uji-t adalah 1,196. Berdasarkan kriteria yang telah ditetapkan jika signifikansi adalah 0,001 0,005 maka H0 ditolak itu berarti tidak ada pengaruh PLPG dengan kompetensi guru sementara H11 diterimah menunjukkan bahwa pelatihan PLPG mempunyai pengaruh terhadap kompetensi profesional guru